Diversity of Saprotrophic Anamorphic Ascomycetes from native forests in Argentina: an updated review - Allegrucci, Natalia (2009)
Eight regions of native forests have been recognized in Argentina: Chaco forest, Misiones rain forest, Tucumán-Bolivia forest (Yunga), Andean-Patagonian forest, “Monte”, “Espinal”, fluvial forests of the Paraguay, Paraná and Uruguay rivers, and “Talares” in the Pampean region. We reviewed the available data concerning biodiversity of saprotrophic micro-fungi (anamorphic Ascomycota) in those native forests from Argentina, from the earliest collections, done by Spegazzini, to present. Among the above mentioned regions most studies on saprotrophic micro-fungi concentrates on the Andean-Patagonian forest, the fluvial forests of the Paraguay, Paraná and Uruguay rivers and the “Talares”, in the Pampean region. There are only a few records of fungal species in other native forests. No record of anamorphic species of Ascomycota was previously available for “Monte” forests. From a comprehensive bibliographic review, a total of 344 species were registered, of which 81 (23,5%) are new species. This work manifests the lack of explorations in important areas of the country, and demonstrates the need to increase those studies.